Islamic Law and Human Trafficking: The Ethical and Legal Frameworks - Rashdi, Saber (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Human trafficking represents a profound violation of human rights, prompting critical examination across both Islamic and Western legal traditions. This study compares these perspectives, identifying shared values and key distinctions, with particular emphasis on the ethical and punitive aspects of Islamic law related to exploitation. Using a normative legal research methodology, this research investigates the role of Islamic law (Sharia) in countering human trafficking, viewed as a contemporary form of slavery. Through an analysis of Sharia principles, such as the sanctity of human life and the comprehensive prohibition against exploitation, this study reveals preventive strategies embedded within Islamic jurisprudence. These strategies include the elimination of exploitation sources and the prohibition of unjust enrichment at the expense of vulnerable populations. The study further advocates for an integrated approach that addresses both the physical and moral dimensions of human protection. In conclusion, this research affirms Islamic law as a comprehensive framework that aligns with international human rights efforts, notably in its decisive opposition to human exploitation and commodification.